2021
DOI: 10.1051/e3sconf/202128009004
|View full text |Cite
|
Sign up to set email alerts
|

The essence and mechanisms of environmental competence formation in students of natural science departments

Abstract: A comparative analysis of the ecological (environmental) educational component of the training in students of Natural Science Departments (Chemistry, Biology, Earth Sciences, Ecology) and future teachers of natural sciences has been carried out. The general and professional competences, program results of training, and applicants training educational programs on the example of several Ukrainian universities are analyzed. It is revealed that the formation of environmental competence is carried out by acquiring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 5 publications
(2 reference statements)
0
2
0
1
Order By: Relevance
“…This was necessary to carry out analysis and effectively manage the activities of students participating in the experiment, as well as to exclude the possibility of obtaining random results of the experiment. The results of experimental training indicate that the developed model of the methodology for the development of research activities in the training of students of biologists is effective and can be applied to the content of the disciplines "Invertebrate Zoology" and "Vertebrate Zoology" in pedagogical universities, in the system of advanced training of biologists (Romaniuk et al, 2021). Thus, the logical set of solutions to the tasks set proved the validity of the theoretical positions put forward during the research.…”
Section: Discussionmentioning
confidence: 80%
“…This was necessary to carry out analysis and effectively manage the activities of students participating in the experiment, as well as to exclude the possibility of obtaining random results of the experiment. The results of experimental training indicate that the developed model of the methodology for the development of research activities in the training of students of biologists is effective and can be applied to the content of the disciplines "Invertebrate Zoology" and "Vertebrate Zoology" in pedagogical universities, in the system of advanced training of biologists (Romaniuk et al, 2021). Thus, the logical set of solutions to the tasks set proved the validity of the theoretical positions put forward during the research.…”
Section: Discussionmentioning
confidence: 80%
“…The research of the authors (Romaniuk R. et al, 2021) is important, in which it was found that the formation of environmental competence is carried out by obtaining environmental education using interactive technologies, forms and methods of organizing the educational process. The article confirms the positive impact of involving students in research, nature conservation, ecological and naturalistic work during extra-curricular hours on the formation of their environmental competence.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Esos programas de EA al interior de las empresas permiten el desarrollo del conocimiento, la comprensión y el sentido de la responsabilidad hacia el medio ambiente (Dilli, 2016), ya que contribuyen a la formación de competencias medioambientales que mejoran su currículo (Romaniuk et al, 2021); además, los propietarios-gestores de pequeñas empresas destacan la importancia de una EA que utilice un lenguaje sencillo, ofrezca contenidos prácticos y proporcione información, utilizando fuentes de confianza (Redmond & Walker, 2009).…”
Section: La Industria Y La Eaunclassified